Gambaran Pemahaman Dan Kesiapan Belajar Siswa - Siswi Melalui Layanan Bimbingan Konseling di SMP CERDAS MURNI DAN SMP BUDI SATRYA - khairani syam manurung; Ade Chita Putri Harahap; Mahvira Aulia Lubis; Amanda Zulfani Harahap; Azlika Zuinu Rahma Sirait; Suvika Syahputri; Maruba Aliana Daulay; Mutiara Fadilah Al Panzil (Peneliti.net, 2023)
This study aims to provide an overview of students' understanding and readiness for the learning process obtained through guidance and counseling services. Therefore, researchers are looking for schools that provide guidance and counseling services to express students' understanding and readiness to learn. CERDAS MURNI Middle School and BUDI SATRYA Middle School are schools that provide guidance and counseling services to find out students' understanding and learning readiness. The method used in this study is a qualitative method by interviewing counseling teachers at both junior high schools as counseling teachers who provide guidance and counseling. The results of the study show that through guidance and counseling, students who understand and are ready to learn have good cognitive abilities, high interest in learning, and strong learning motivation.